2013
DOI: 10.1167/iovs.12-10228
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 as a Predictive Biomarker for Metastatic Uveal Melanoma in Humans

Abstract: PURPOSE. High expression levels of insulin-like growth factor-1 (IGF-1) receptor were associated with metastatic uveal melanoma (UM). The purpose of this study was to examine the potential of serum IGF-1 in early detection of liver metastasis.METHODS. IGF-1 serum levels were analyzed using enzymelinked immunosorbent assay for 118 subjects in three different groups: 55 disease-free (DF) UM patients who did not develop metastasis within 10 years of diagnosis; 22 metastatic patients; and 41 healthy subjects. Matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Multiple studies have reported overexpression of IGF-1 receptors in various cancers, including uveal melanoma; therefore, the effects of insulin on cancer cell Sensitivity proliferation in vivo are believed to be indirectly related to IGF-1 production, which has proliferative and antiapoptotic effects and increases the levels of VEGF by upregulating growth hormone receptors in the liver and by decreasing insulin-binding proteins [8,12,21]. In uveal melanoma, IGF-1-receptor positive tumor cell ratios have been associated with a poor prognosis [22], and serum IGF-1 levels were found to be related to scleral invasion [12] and liver metastasis [8]. Osteopontin, S100b, melanoma-inhibiting antigen, VEGF, and DJ-1 were also shown to be the increased parameters identified in metastatic disease [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have reported overexpression of IGF-1 receptors in various cancers, including uveal melanoma; therefore, the effects of insulin on cancer cell Sensitivity proliferation in vivo are believed to be indirectly related to IGF-1 production, which has proliferative and antiapoptotic effects and increases the levels of VEGF by upregulating growth hormone receptors in the liver and by decreasing insulin-binding proteins [8,12,21]. In uveal melanoma, IGF-1-receptor positive tumor cell ratios have been associated with a poor prognosis [22], and serum IGF-1 levels were found to be related to scleral invasion [12] and liver metastasis [8]. Osteopontin, S100b, melanoma-inhibiting antigen, VEGF, and DJ-1 were also shown to be the increased parameters identified in metastatic disease [8].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the method for detecting metastasis is a combination of blood tests with abdominal imaging. However, neither the currently available serum biomarkers nor the imaging methods provide a long enough lead time for a complete surgical resection of the liver metastasis to be performed [8]. Thus, it is very important to find reliable serum biomarkers to identify the patients at high risk for the development of metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that serial IGF-1 levels may have a role as a predictive biomarker for metastatic uveal melanoma when measured repeatedly in one individual. 49 Triozzi et al studied 76 treated primary uveal melanoma patients and found a correlation between the presence of monosomy 3 and human leukocyte antigen-class-I-associated β-2 microglobulin (P≤0.02). Based on the strong association between monosomy 3 and development of metastatic disease, the authors concluded that the microglobulin may have a potential role as a screening tool for metastatic disease.…”
Section: Surveillance and Treatments For Metastatic Diseasementioning
confidence: 99%
“…The molecular prognostic factors comprise the presence of mRNA tyrosinase, vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), and insulin-like growth factor-1 (ILGF-1) [12][13][14][15]. The risk factors of the chromosome aberration and gene mutations refer to the loss of one copy of chromosome 3 (monosomy), doubling of chromosome 8, mutation in GNAQ and GNA11 genes, СС genotype of polymorphic C3435T marker of ABCB1 gene and a number of other changes [3,10,[16][17][18][19].…”
mentioning
confidence: 99%